2003
DOI: 10.1016/s1672-0229(03)01015-5
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Characterization and Antigenicity of the S Protein of SARS-CoV

Abstract: The corona-like spikes or peplomers on the surface of the virion under electronic microscope are the most striking features of coronaviruses. The S (spike) protein is the largest structural protein, with 1,255 amino acids, in the viral genome. Its structure can be divided into three regions: a long N-terminal region in the exterior, a characteristic transmembrane (TM) region, and a short C-terminus in the interior of a virion. We detected fifteen substitutions of nucleotides by comparisons with the seventeen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The focus of this study was to predict both B-cell and T-cell epitopes using the S protein of SARS-CoV-2 by immunoinformatics method. S protein of SARS-CoV-2 was selected for its immunogenicity along with the important role in viral attachment to the host cell surface [ 48 , 49 , 50 ]. Also, epitopes of viral S protein (such as SARS-CoV S protein) are the most antigenic part that elicit an intrinsic immunogenic response by signaling immune cells to increase both humoral and adaptive immunity [ 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The focus of this study was to predict both B-cell and T-cell epitopes using the S protein of SARS-CoV-2 by immunoinformatics method. S protein of SARS-CoV-2 was selected for its immunogenicity along with the important role in viral attachment to the host cell surface [ 48 , 49 , 50 ]. Also, epitopes of viral S protein (such as SARS-CoV S protein) are the most antigenic part that elicit an intrinsic immunogenic response by signaling immune cells to increase both humoral and adaptive immunity [ 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initial analysis of the 1255-a.a. peplomer protein of the virus reveals the possible existence of a signal peptide that would likely be cleaved between residues 13 and 14 ( 12 ). The whole structure is predicted to contain a receptor-binding unit (S1) in the N-terminus 14., 25., 26., 27. and a transmembrane unit (S2) in the C-terminus 13., 14., 25., 27.. Molecular modeling of the S1 and S2 subunits of the spike glycoprotein 26., 28. suggested that the former unit is consisted of mainly anti-parallel β -sheets with dispersed α and β regions, in addition to the three domains identified in the S2 unit.…”
Section: Molecular Biology Of Sars-covmentioning
confidence: 99%